External Capital Structure : Theory and Evidence - Lane, Philip; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 2000)
Recent years have witnessed a change in the composition of capital flows to developing countries, and FDI and equity flows have been playing an increasing role. In this paper we discuss the challenges for international macroeconomics that these developments pose and characterize stylized facts associated with the structure of external liabilities in developing countries, focusing in particular on FDI and equity stocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet